2018
DOI: 10.3390/ma11101903
|View full text |Cite
|
Sign up to set email alerts
|

Grain Refinement by Second Phase Particles under Applied Stress in ZK60 Mg Alloy with Y through Phase Field Simulation

Abstract: Based on the principle of grain refinement caused by the second-phase particles, a phase field model was built to describe the recrystallization process in the ZK60 alloy system with Y added under applied stress between temperatures 573 and 673 K for 140 min duration. The simulation of grain growth with second phase particles and applied stress during annealing process on industrial scale on the condition of real time-space was achieved. Quantitative analysis was carried out and some useful laws were revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The nano-grained metals have attracted great attention due to their excellent properties for the structure designed [ 29 , 30 ]. Since the grain growth process is widely simulated through the phase field model [ 4 , 31 , 32 ], this lattice model can take into account the grain lattice direction in the elastic contribution of the total free energy. It should be noted that no specific material is employed.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The nano-grained metals have attracted great attention due to their excellent properties for the structure designed [ 29 , 30 ]. Since the grain growth process is widely simulated through the phase field model [ 4 , 31 , 32 ], this lattice model can take into account the grain lattice direction in the elastic contribution of the total free energy. It should be noted that no specific material is employed.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…While studying the effect of second phase particles of Y on ZK60 Mg alloy, Song Y. et al [31] showed that second phase particles results in a microstructure of fine grains.…”
Section: Severe Plastic Deformationmentioning
confidence: 99%
“…These observed improvements in hydrogen properties are the result of interrelated parameters associated with particle size. While studying the effect of second phase particles of Y on ZK60 Mg alloy, Song Y. et al [31] showed that second phase particles results in a microstructure of fine grains.…”
Section: Mechanical Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…phase is slightly finer as compared to BCC1 (Table 2). As the BCC2 phase fraction increases, the size of BCC1 phase is slightly decreased with milling time due to the increase in grain size strengthening effect [28]. Figure 2a, b displays the XRD patterns of the bulk LWHEA after densification at 600 and 700 °C.…”
Section: Phase Evolution Of Powder and Bulk Lwheamentioning
confidence: 99%